A Distinct Subpopulation of Bone Marrow Mesenchymal Stem Cells, Muse Cells, Directly Commit to the Replacement of Liver Components. Issue 2 (11th December 2015) - Katagiri, H.; Kushida, Y.; Nojima, M.; Kuroda, Y.; Wakao, S.; Ishida, K.; Endo, F.; Kume, K.; Takahara, T.; Nitta, H.; Tsuda, H.; Dezawa, M.; et al.
Abstract : Genotyping graft livers by short tandem repeats after human living‐donor liver transplantation (n = 20) revealed the presence of recipient or chimeric genotype cases in hepatocytes (6 of 17, 35.3%), sinusoidal cells (18 of 18, 100%), cholangiocytes (15 of 17, 88.2%) and cells in the periportal areas (7 of 8, 87.5%), suggesting extrahepatic cell involvement in liver regeneration. Regarding extrahepatic origin, bone marrow mesenchymal stem cells (BM‐MSCs) have been suggested to contribute to liver regeneration but compose a heterogeneous population. We focused on a more specific subpopulation (1–2% of BM‐MSCs), called multilineage‐differentiating stress‐enduring (Muse) cells, for their ability to differentiate into liver‐lineage cells and repair tissue. We generated a physical partial hepatectomy model in immunodeficient mice and injected green fluorescent protein (GFP)‐labeled human BM‐MSC Muse cells intravenously (n = 20). Immunohistochemistry, fluorescence in situ hybridization and species‐specific polymerase chain reaction revealed that they integrated into regenerating areas and expressed liver progenitor markers during the early phase and then differentiated spontaneously into major liver components, including hepatocytes (≈74.3% of GFP‐positive integrated Muse cells), cholangiocytes (≈17.7%), sinusoidal endothelial cells (≈2.0%), and Kupffer cells (≈6.0%). In contrast, the remaining cells in the BM‐MSCs were not detected in the liver for up to 4 weeks. These results suggest that Muse cells are the predominant population of BM‐MSCs that are capable of replacing major liver components during liver regeneration.